Pengembangan Kompetensi Sosial pada UMKM dan SDGs dalam Program KKN di Desa Tirem Gresik - Muhammad Ainul Yaqin; Galang Kiswantoro; Aldi Tri Saputra; Berlian Bayhaqi; Narinda Lailatus Amy; Annisa Sholikhatun Nur Ramawati; Handah; Stevanus Edi Saputra Sinaga; Pudji Setiawan; Fiki Dadang Kuncoro (GOTAVA, 2024)
Kuliah Kerja Nyata (KKN) is a form of activity that combines the Dharma of Education, Teaching, Research, and Community Service all in one activity. As educational and teaching activities. KKN is an integral part of the undergraduate higher education curriculum (S1). KKN participants must be able to adjust to the existing reality, and not only understand theory, but must be able to apply and learn from the experiences that we have in the community, especially in the village of Tirem, which is located in Sitsampeyan District, Gresik Regency, East Java with an area of 107 hectares, has a population of 816 people, with 416 men and 400 women. The survey shows that as much as 60% of the tirem village community work as pond farmers, the rest as factory workers, civil servants, MSME entrepreneurs. The target of the students is to carry out the achievement of SDGs (Sustainable Development Goals) "including maintenance of pond diesel engines, advancing regional MSMEs to the modernization era, socialization of NIB licensing arrangements.